Density Functional Theory-Assisted Synthesis of Self-Curing Epoxy–Acrylic Resin - Yang, Bowen; An, Qiufeng (Frontiers in Chemistry, 2021)
A density functional theory-assisted synthesis of self-curing epoxy–acrylic resin (EMPA) is described. The calculated quantum chemistry reaction index of the reacting monomer in the basic state, i.e., the radical reaction index (Fk0), is used as a guide to optimize the synthesis conditions. The reliability of the Fk0-assisted synthesis method is confirmed after evaluating the physical appearance, mechanical properties after curing, and thermal stability of the obtained EMPA. The special functional groups of the resin are characterized by Fourier transform infrared spectroscopy to prove the rationality of the reaction mechanism. The cross-sectional morphology characteristics of the cured resin are observed by field-emission scanning electron microscopy. The results show that the closer the molar ratio of monomers in the reaction to the ratio of Fk0 of the reacting monomers, the better the polymerization performance.